2021
DOI: 10.1155/2021/3491509
|View full text |Cite|
|
Sign up to set email alerts
|

Study on the Application Value of CT Thin-Layer Scan Data Assisted 3D Printing Technology in Hip and Knee Replacement

Abstract: To better study hip and knee replacement, 50 eligible hip and knee patients from March 2020 to April 2021 were selected. A 1 : 1 scale solid model was printed with CT thin-layer scanning data assisted by 3D printing technology to evaluate the ankle function of patients six months after surgery. The results showed that the 3D rapid prototyping time of the 1 : 1 fracture model in 50 patients was 3-4 hours. The operation time was 70–90 min, and the average operation time was 80 min. The actual application in oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Periapatite being a highly crystalline l i q u i d a l l ow s f o r b e tte r c oat i ng demonstrated by decreased migration of tibial components at 10 years as compared to uncoated ones on RSA [66]. Periapatite coating has shown similar clinical results and loosening rates as compared to titanium coating over trabecular metal [67].…”
Section: Periapatite Coatingmentioning
confidence: 99%
“…Periapatite being a highly crystalline l i q u i d a l l ow s f o r b e tte r c oat i ng demonstrated by decreased migration of tibial components at 10 years as compared to uncoated ones on RSA [66]. Periapatite coating has shown similar clinical results and loosening rates as compared to titanium coating over trabecular metal [67].…”
Section: Periapatite Coatingmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%